Handbook of Qualitative Health Research for Evidence-Based Practice - Olson, Karin; Young, Richard A.; Schultz, Izabela Z. (Handbooks in Health, Work, and Disability, 2016)
This progressive reference redefines qualitative research as a crucial component of evidence-based practice and assesses its current and future impact on healthcare. Its introductory section explains the value of sociocultural context in case conceptualization, and ways this evidence can be integrated with quantitative findings to inform and transform practice. The bulk of the book's chapters review qualitative research in diverse areas, including pain, trauma, heart disease, COPD, and disabling conditions, and examine ways of effectively evaluating and applying qualitative data. This seismic shift in perception moves the healing professions away from traditional one-size-fits-all thinking and toward responsive, patient-centered care. Among the topics in the Handbook: ·Examining qualitative alternatives to categorical representation. ·The World Health Organization model of health: what evidence is needed? ·Qualitative research in mental health and mental illness. ·Qualitative evidence in pediatrics. ·The contribution of qualitative research to medication adherence. ·Qualitative evidence in health policy analysis. The Handbook of Qualitative Health Research for Evidence-Based Practice offers health and clinical psychologists, rehabilitation specialists, occupational and physical therapists, nurses, family physicians and other primary care providers new ways for understanding patients' health-related experiences and opens up new ways for developing interventions intended to improve health outcomes.